Principles of biochemistry (Pearson, 2014)
Principles of Biochemistry provides a concise introduction to fundamental concepts of biochemistry, striking the right balance of rigor and detail between the encyclopedic volumes and the cursory overview texts available today. Widely praised for accuracy, currency, and clarity of exposition, the Fifth Edition offers a new student-friendly design, an enhanced visual program, new Application Boxes, contemporary research integrated throughout, and updated end-of-chapter problems.